French Revolution and human rights : a brief documentary history a brief documentary history - Hunt, Lynn, 1945- (Boston : Bedford Books of St. Martin's Press, 1996)
This brief documentary history explores the issue of rights and citizenship that dominated Revolutionary France and helped define modern notions of civil rights. The rich selection of 38 primary documents - many never before published in English allows students to read and analyze, firsthand, the intense debates and subsequent legislation engendered by the French Revolution. An extensive introductory essay discusses the controversies over citizenship and rights current in Enlightenment and Revolutionary France. Headnotes for the documents, a chronology, a bibliography, engravings from the period, and questions to consider are also included.
The revolutionary origins of human rights -- The documents -- Defining rights before 1789 -- The declaration of the rights of man and citizen, 1789 -- Debates over citizenship and rights during the revolution.
Includes bibliographical references (pages 146-147) and index.
Keywords: Politics and culture -- France -- History -- 18th century -- Sources; Human rights -- France -- History -- Revolution, 1789-1794 -- Sources; France -- History -- Revolution, 1789-1799 -- Social aspects -- Sources